“My Name is Nothing Extra/But the Truth to you I'll Tell”:Assessing the Personal Use of Traditional Poetry - Baldwin, Karen (Ethnologies, 1993)
Traditional poet Roscoe Solley composed and recited from a body of occasional and family poems for 50 years. A young man in the early 20th century when poem recitation was a common community activity in his central Pennsylvania area, Solley revived his poemcraft in the 1970s, extended his array of subjects, and performed for culturally different audiences, using his verses as Personal communication and as a means to create audiences of occasion he then poetically commemorated.